2020
DOI: 10.1371/journal.pbio.3000891
|View full text |Cite
|
Sign up to set email alerts
|

Interphase-arrested Drosophila embryos activate zygotic gene expression and initiate mid-blastula transition events at a low nuclear-cytoplasmic ratio

Abstract: Externally deposited eggs begin development with an immense cytoplasm and a single overwhelmed nucleus. Rapid mitotic cycles restore normality as the ratio of nuclei to cytoplasm (N/C) increases. A threshold N/C has been widely proposed to activate zygotic genome transcription and onset of morphogenesis at the mid-blastula transition (MBT). To test whether a threshold N/C is required for these events, we blocked N/C increase by down-regulating cyclin/Cdk1 to arrest early cell cycles in Drosophila. Embryos that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 86 publications
0
29
0
Order By: Relevance
“…An important and recently debated ( Strong et al, 2020 ; Syed et al, 2021 ) example of such a potentially autonomous developmental timing mechanism that can run independently of the cell cycle progression is the program that triggers cellularization during mid-blastula transition (MBT) in embryogenesis ( Figure 3A ). Organismal development unfolds on a tight schedule and in specific sequences that are unlikely to be reproduced by stochasticity.…”
Section: The Emerging Concept Of Autonomous Clocks and Their Mechanisms At Different Scales And Complexitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…An important and recently debated ( Strong et al, 2020 ; Syed et al, 2021 ) example of such a potentially autonomous developmental timing mechanism that can run independently of the cell cycle progression is the program that triggers cellularization during mid-blastula transition (MBT) in embryogenesis ( Figure 3A ). Organismal development unfolds on a tight schedule and in specific sequences that are unlikely to be reproduced by stochasticity.…”
Section: The Emerging Concept Of Autonomous Clocks and Their Mechanisms At Different Scales And Complexitiesmentioning
confidence: 99%
“…The major temporal trigger of maternal-to-zygotic transition and its associated events – both in flies and other species – has long been assumed to be the exponential increase in nuclear-to-cytoplasmic (N/C) ratio as a function of cell cycle progression ( Edgar et al, 1986 ; Newport and Kirschner, 1982 ). With elegant experiments that genetically perturb the progression of cell cycle in fly embryos, recent work suggests the contrary: neither the activation of zygotic genome nor the timing of cellularization is governed by an accurate N/C ratio or cell cycle progression, and both events appear to occur when the nuclear divisions are halted 2–3 rounds in prior ( Figure 3A ; McCleland and O’Farrell, 2008 ; Strong et al, 2020 ). These experiments also reveal a subtle but critical difference between the onset times of cellularization and the zygotic genome activation.…”
Section: The Emerging Concept Of Autonomous Clocks and Their Mechanisms At Different Scales And Complexitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent RNA-seq has shown that the vast majority of genes, including the genes used in this study, are capable of initiating detectable transcription if the cell cycle is stopped one or two cycles prematurely (33). This demonstrates that pre-ZGA N/C ratios are not strictly incompatible with transcription.…”
Section: Discussionmentioning
confidence: 62%
“…In Drosophila and zebrafish, it has been observed that the early interphases simply are not long enough to sustain robust transcription of most genes (20,21,(29)(30)(31)(32). One recent study found that if the cell cycle is artificially paused, the vast majority of ZGA genes can be induced one or two cell cycles prematurely in Drosophila (33). On the other hand, ZGA has been implicated as upstream of cell cycle slowing.…”
mentioning
confidence: 99%